Argentina : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
Domestic and external factors combined to bring about the loss of confidence in Argentina that triggered the debt default and the crisis. Restoring confidence in legal certainty has been a major challenge for Argentina. The fiscal program is centered on maintaining tight control over primary spending and rebuilding the tax administration. A key outstanding issue is to close the estimated fiscal and external financing gap. The fiscal effort required to sustain the public finances in the medium term will require the adoption of major structural reforms.